Approaches in Transactional Analysis Counseling According to Berne's Perspective - Pu’ad Maulana; Netrawati; Zadrian Ardi; Rahmad Firmansyah; Thessia Permata Bunda (Journal Of Psychology, Counseling And Education, 2025)
Transactional analysis (AT) is one type of transactional therapy that can be used in individual therapy. However, it differs from other AT therapies in that it is more suitable for group therapy. Mainly because it is a conventional and optional treatment. Relationship is the connection between one person and another. The factors evaluated include communication and content. In this recovery, the relationship between client and consultant is viewed as a transaction (interaction, work, research), where each participant engages the other as a function of some goal.